2021
DOI: 10.31659/0585-430x-2021-789-3-39-44
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Resistance of Sulfur-Extended Asphalt Concrete. Results of the Study and Features of Definition

Abstract: применение сероасфальтобетонных композиционных покрытий на автомобильных дорогах и мостах // Интернет-журнал «НАУКОВЕДЕНИЕ» Том 8, №3 (2016) http://naukovedenie.ru/PDF/104TVN316.pdf (доступ свободный). Загл. с экрана. Яз. рус., англ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Further improvement of the technology Materials 2021, 14, 7218 2 of 10 of sulfur asphalt concrete is presented in [18]. Nevertheless, in works [19][20][21] it is shown that sulfur-asphalt concrete is characterized by insufficiently high water resistance with prolonged water saturation. The reasons for this may be [21]:…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further improvement of the technology Materials 2021, 14, 7218 2 of 10 of sulfur asphalt concrete is presented in [18]. Nevertheless, in works [19][20][21] it is shown that sulfur-asphalt concrete is characterized by insufficiently high water resistance with prolonged water saturation. The reasons for this may be [21]:…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in works [19][20][21] it is shown that sulfur-asphalt concrete is characterized by insufficiently high water resistance with prolonged water saturation. The reasons for this may be [21]:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations